2013
DOI: 10.1158/0008-5472.can-13-0122-t
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Sustains Melanoma Proliferation and Represents a New Target for Epigenetic Therapy

Abstract: Metastatic melanoma remains a mostly incurable disease. Although newly approved targeted therapies are efficacious in a subset of patients, resistance and relapse rapidly ensue. Alternative therapeutic strategies to manipulate epigenetic regulators and disrupt the transcriptional program that maintains tumor cell identity are emerging. Bromodomain and extraterminal domain (BET) proteins are epigenome readers known to exert key roles at the interface between chromatin remodeling and transcriptional regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
201
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(221 citation statements)
references
References 52 publications
10
201
1
Order By: Relevance
“…To assess whether RVX2135 affects cell types other than Myc-induced lymphoma, we cultured five melanoma cell lines in the absence or presence of 10 μM RVX2135. Similar to previous studies on a different BET inhibitor (18), RVX2135 suppressed cell-cycle progression (Fig. S3A).…”
Section: Rvx2135 Blocks Proliferation Of Myc-induced Mouse Lymphoma Csupporting
confidence: 89%
See 1 more Smart Citation
“…To assess whether RVX2135 affects cell types other than Myc-induced lymphoma, we cultured five melanoma cell lines in the absence or presence of 10 μM RVX2135. Similar to previous studies on a different BET inhibitor (18), RVX2135 suppressed cell-cycle progression (Fig. S3A).…”
Section: Rvx2135 Blocks Proliferation Of Myc-induced Mouse Lymphoma Csupporting
confidence: 89%
“…The in vivo data presented here and previous studies using other BETi have shown that inhibition of BET proteins is tolerated in mice (3,18,44,45). BETi exhibit broad transcriptional effects by targeting the general transcriptional elongation factor p-TEFb's interplay with Brd4.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have demonstrated that BRD4 promotes cell cycle progression and regulates cell growth and transcription (13). Subsequent studies have demonstrated that BRD4 serves a critical role in tumor proliferation and growth in melanoma (14), neuroblastoma (15), glioblastoma (16), malignant peripheral nerve sheath tumors (17), lymphoblastic leukemia (18) and lung adenocarcinoma (19). However, to the best of our knowledge, the involvement of BRD4 in migration and invasion has not been reported in HCC.…”
Section: Introductionmentioning
confidence: 98%
“…Based on our observation that H2A.Z.2 loss has a dramatic effect on histone acetylation and BRD2 cellular levels, we queried whether its deficiency could cooperate with BET inhibition. 9 Intriguingly, whereas in control cells the BET inhibitor JQ1 10 exerts a cytostatic effect, cells depleted of H2A.Z.2 that are treated with the same doses of JQ1 die by apoptosis. In addition, H2A.Z.2 deficiency sensitizes melanoma cells to chemotherapy and to MEK inhibitors.…”
mentioning
confidence: 99%